(untitled) (Clinics, 2019)
OBJECTIVES: This is a randomized controlled trial that aims to evaluate the impact of pharmacist-led discharge counseling on reducing pharmacotherapy problems in the 30-day postdischarge period of cardiology patients from a tertiary hospital in Brazil. METHODS: At discharge, two cardiovascular pharmacy residents performed a medication counseling session with the intervention group, and the follow-up was performed by telephone (3 and 15 days after discharge). The number of pharmacotherapy problems was evaluated during a pharmacist-led ambulatory consultation 30 days after discharge. RESULTS: A total of 66 and 67 patients were randomized to the intervention and control groups, respectively, but only 51 patients were analyzed in each group, all with similar baseline characteristics. The intervention group had significantly fewer pharmacotherapy problems compared to the control (po0.001), and 100% of the patients had at least one problem. We observed five problems significantly more frequently in the control group: ‘‘incorrect time of taking’’ (p=0.003), ‘‘use higher dose of medication’’ (p=0.007), ‘‘use lower dose of medication’’ (p=0.014), ‘‘restart discontinued medication’’ (p=0.011), and ‘‘underdosing prescription’’ (p=0.009). Simvastatin, enalapril, carvedilol, and atorvastatin were the medications more associated with pharmacotherapy problems. CONCLUSIONS: We concluded that pharmacist-led discharge counseling should be an indispensable service, as patients exhibited less pharmacotherapy problems in the 30-day postdischarge period, especially related to drug administration and adherence.